Formulación de una galleta a partir de harina de tarwi (Lupinus mutabilis Sweet) y trigo (Triticum L.) rellena con mucílago de cacao - Cabrera Mera, Víctor Jhoel (2022)
Considering that the development of a formulation is very important for the survival of a product in the market, this work aims to formulate a biscuit from tarwi flour (Lupinus mutabilis Sweet) and wheat (Triticum L.) filled with cocoa mucilage